The Conquest of Constantinople - Mohammad-e Taheri (تاریخ اسلام, 2007)
One of the most important events in the history of Islam and even the history of the world is the conquest of Constantinople, the capital of the Byzantine Empire, by the Ottoman Sultan Mehmed II the Conqueror. This major historical event not only comprises numerous significant aspects by itself, but also requires much additional study and research because of the various effects and consequences it has had in the political and economic developments of the globe afterwards. What you will be presented with in this article is the strategy of the Ottoman assault on Constantinople, the situation inside the city while under attack, the gradual fall of the city, and major aftermaths of the conquest of the city by the Ottomans. Considering the necessity to abridge the material in this paper, the author has tried to deal only with the most important and interesting aspects and dimensions of this historical incident and refrain from discussing details of separate events related to the fall of the city.